Sex differences in group 2 innate lymphoid cell-dominant allergic airway inflammation. (December 2020) - Wang, Cong; Xu, Zhi-Bin; Peng, Ya-Qi; Zhang, Hong-Yu; Yu, Qiu-Ning; Guo, Yu-Biao; Tan, Wei-Ping; Liu, Yang-Li; Meng, Xiang-Ci; Fang, Shu-Bin; Chen, Dong; Fu, Qing-Ling
Highlights: Female mice with ILC2-dominant allergic airway inflammation exhibited higher levels of ILC2 levels compared to male mice. The treatment of testosterone significantly decreased the intracellular type 2 cytokines ILC2. Testosterone suppressed the proliferation of ILC2s. Abstract: There were gender differences in the prevalence and severity of allergic diseases. Group 2 innate lymphoid cells (ILC2s) were recently reported to play a critical role in allergic diseases. We investigated the sex-dependent differences in ILC2-dominant allergic airway inflammation model using T\B cell-deficient mice, and determined the gender differences of ILC2 levels in patients with asthma and allergic rhinitis. Female mice exhibited higher levels of inflammatory infiltration and large production of IL-5 and IL-13, especially for ILC2 levels compared to male mice with the induction of IL-33. However, no significant differences were found for the levels of circulating ILC2s between the genders of patients. The treatment of testosterone significantly decreased the intracellular type 2 cytokines in ILC2s and the proliferation of pure ILC2s in response to epithelial cytokines. Our study suggested the sex differences and the involvement of androgen on ILC2s in allergic diseases.